High molecular weight organic compounds (HMW-OCs) in severe winter haze: Direct observation and insights on the formation mechanism. (November 2016) - Duan, F.K.; He, K.B.; Ma, Y.L.; Ihozaki, T.; Kawasaki, H.; Arakawa, R.; Kitayama, S.; Tujimoto, K.; Huang, T.; Kimoto, T.; Furutani, H.; Toyoda, M.
Abstract: High molecular weight organic compounds (HMW-OCs), formed as secondary organic aerosols (SOA), have been reported in many laboratory studies. However, little evidence of HMW-OCs formation, in particular during winter season in the real atmosphere, has been reported. In January 2013, Beijing faced historically severe haze pollution, in which the hourly PM2.5 concentration reached as high as 974 μg m −3 . Four typical haze events (HE1 to HE4) were identified, and HE2 (Jan. 9–16) was the most serious of these. Based on the hourly observed chemical composition of PM2.5 and the daily organic composition analyzed by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS), we found that abundant ion peaks in m/z 200–850 appeared on heavy haze days, whereas these were negligible on a clear day, indicating the existence of HMW-OCs in the wintertime haze. A negative nonlinear correlation between HMW-OCs and O3 suggested that gas oxidation was not likely to be the dominant mechanism for HMW-OCs formation. During the heavy haze events, the relative humidity and mass ratio of H2 O/PM2.5 reached as high as 80% and 0.2, respectively. The high water content and its good positive correlation with HMW-OCs indicated that an aqueous-phase process may be a significant pathway in wintertime. The evidence that acidity was much higher during HE2 (0.37 μg m −3 ) than on other days, as well as its strong correlation with HMW-OCs, indicated that acid-catalyzed reactions likely resulted in HMW-OCs formation during the heavy winter haze in Beijing. Graphical abstract: Highlights: High molecular weight organic compounds (HMW-OCs) in PM2.5 during winter haze pollution are observed directly. The acidity of aerosol and water content play important roles in the formation of HMW-OCs. Gas oxidation was probably not the dominant mechanism for HMW-OCs formation in winter. Our findings have important implications for SOA formation and for the model improvement. Abstract : The aerosol acidity and water content played more important roles than O3 oxidation in the formation of HMW-OCs during winter haze.